Distribuição de recrutas e adultos de cinco espécies de peixes recifais do Atol das Rocas - Paiva, Carolina Cerqueira de (2008)
The success in the recruitment of reef fish depends on the number of individuals who survive after larvae have entered in the reef environment. Different post-recruitment processes are responsible for the distribution of recruits and adults and consequently, for the structure of their populations. The distribution of Abudefduf saxatilis, Stegastes rocasensis, Thalassoma noronhanum, Acanthurus chirurgus and Acanthurus coeruleus recruits and adults were assessed through visual censuses in the Atol das Rocas. 13 sample stations with contrasting features were pooled in five categories: nine pools, a tidal pond formation, a patch reef formation, a sandstone reef and an algae crest. Pools were classified as connected (Barretinha, Barreta Falsa and Podes Crer) and non-permanently connected (Farol 2, Garoupinha, Cemitério, Âncoras, Abrolhos and Tartarugas) with the ocean. Non-connected pools were classified in shallow (Farol 2, Garoupinha and Cemitério) and deep (Âncoras, Abrolhos and Tartarugas). Unifactorial analysis of variance revealed that tidal ponds and pools were the most preferred categories among recruits, while the majority of adults avoided tidal ponds. Independent t-tests per groups demonstrated that the type of pool connectivity with the ocean affected the distribution of the largest part of recruits, however to a much lesser extent in the case of adults. Non-connected pool depth affected the distribution of most recruits and all adults. Migratory movements, structural complexity, reef substrate coverage, the presence of conspecifics, food availability and predator presence are post-recruitment processes that probably affected recruit and adult distribution. Depth may have also influenced A. chirurgus, A. saxatilis recruits and A. coeruleus adults to a certain extent. No A. coeruleus recruits have been observed.